2021
DOI: 10.25289/ml.2021.10.2.90
|View full text |Cite
|
Sign up to set email alerts
|

Polydeoxyribonucleotide and Microlens Array-type, Nanosecond-domain Neodymium:Yttrium-aluminum-garnet Laser Treatment for Scars from Costal Cartilage Harvest Surgery: Case Series of 9 Patients

Abstract: Background and ObjectivesSurgery for harvesting costal cartilage is often required for revision septorhinoplasty due to a lack of septal cartilage in patients with a severely contracted nose, and postoperative scarring on the anterolateral rib cage commonly requires additional treatment. This study aimed to evaluate the therapeutic efficacy and safety of combined polydeoxyribonucleotide (PDRN) and microlens array (MLA)-type nanoseconddomain neodymium (Nd):yttrium-aluminum-garnet (YAG) laser treatment for posto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Another study by Ahn et al [6] reported the effects of PDRN and microlens arrayed type nanosecond-domain Nd:YAG laser combination therapy on postoperative scarring after costal cartilage harvest surgery, further supporting the wound healing-promoting results of PDRN. Ablative CO2 fractional lasers have been used and studied for many years to treat various dermatological conditions, including different types of scars.…”
Section: Discussionmentioning
confidence: 84%
“…Another study by Ahn et al [6] reported the effects of PDRN and microlens arrayed type nanosecond-domain Nd:YAG laser combination therapy on postoperative scarring after costal cartilage harvest surgery, further supporting the wound healing-promoting results of PDRN. Ablative CO2 fractional lasers have been used and studied for many years to treat various dermatological conditions, including different types of scars.…”
Section: Discussionmentioning
confidence: 84%
“…Second, we failed to assess the efficacy of an intra-lesional injection of PDRN in promoting WH. According to a review of the literature, an intra-lesional injection of PDRN has been assessed in the context of plastic and aesthetic surgery [63,64]. Further studies are therefore warranted to assess its efficacy in promoting the healing of diabetic wounds in a murine model of STZ-induced diabetes.…”
mentioning
confidence: 99%